KETAHANAN NASIONAL: KETAHANAN NASIONAL DALAM MEMBANGUN KOLEKTIF KEBANGSAAN - Dasmarni; Hj. Zulhidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyse the role of national resilience in strengthening collective national commitment amid multidimensional threats in the era of globalization and digitalization. The research method used in this study is a qualitative approach employing the Systematic Literature Review (SLR) method. Data were obtained from books, national and international scientific articles, and relevant policy documents published between 2020 and 2025. Data analysis was conducted through the stages of identification, classification, and synthesis of findings to identify patterns in the relationship between national strategies and community participation in strengthening national resilience. The results indicate that national resilience is no longer solely oriented toward military threats but also encompasses digital, social, economic, and ideological threats. The integration of national strategies, strengthening digital literacy, state defences education, and the internalization of Pancasila values are important factors in enhancing community social resilience. The conclusion of this study emphasizes that strengthening national resilience requires an integrative, adaptive, and participatory approach by positioning society as the main subject in maintaining national unity, stability, and sovereignty in the contemporary era.